EVALUATION OF BASIC FOOTBALL SKILLS IN CLASS VIII STUDENTS OF KUTACANE 2 STATE MIDDLE SCHOOL - Fakhrur Rizal (Jurnal Penelitian Progresif, 2024)
This research is entitled "Evaluation of Basic Football Skills in Students of SMP Negeri 2 Kutacane Class VIII 2023/2024 Academic Year". Football is a team game, each team consists of eleven players, and one of them is a goalkeeper. The aim to be achieved in this research is to find out what basic football skills are in students at SMP Negeri 2 Kutacane class VIII for the 2023/2024 academic year. In this research the researcher took 100% of the total population of 26 students. From the results of research conducted by researchers, on class VIII students of SMP Negeri 2 Kutacane for the 2023/2024 academic year. Based on the total T-Score values ​​for basic football skills in students of SMP Negeri 2 Kutacane for the academic year 2023/2024, the researcher concluded that, middle school students Negeri 2 Kutacane for the 2023/2024 Academic Year has good abilities in practicing basic football skills. The above statement can also be proven by the overall results of all test items where the average T-Score value of all test items is 64.0 which is included in the good category. Based on these results, the researcher suggests to health and recreation physical education teachers in junior high schools to provide regular training for students in order to achieve good performance.